PELATIHAN PEMBUATAN BUNGA ARTIFICIAL DARI SAMPAH PLASTIK KRESEK DI DESA KANGKUNG, KECAMATAN MRANGGEN, KABUPATEN DEMAK - Iman Setiono; Heny Kusumayanti; Pangi Pangi; Ida Hayu Dwimawanti; Budiyono Budiyono; Agus Purwanto; Zulfaidah Aryani (Jurnal Pengabdian Vokasi, 2019)
The use of plastic packaging in today's conditions is very worrying, because the plastic is very difficult and long to decompose will cause environmental pollution. As one way to reduce plastic waste is to make plastic waste into useful items of economic value. To realize this goal, a training was held in the Kangkung Village, Mranggen sub-district, Demak Regency, for Family Welfare Empowerment Members in the local village. The method used is an experiment with direct practice. The results obtained turned out that the plastic flowers were successfully made by Family Welfare Empowerment Members and successfully sold.